2005
DOI: 10.1038/nmeth747
|View full text |Cite
|
Sign up to set email alerts
|

A multiplexed homogeneous fluorescence-based assay for protein kinase activity in cell lysates

Abstract: New methods to quantify protein kinase activities directly from complex cellular mixtures are critical for understanding biological regulatory pathways. Herein, a fluorescence-based chemosensor strategy for the direct measurement of kinase activities in crude mammalian cell lysates is described. We first designed a new fluorescent peptide reporter substrate for each target kinase. These kinase chemosensors were readily phosphorylated by recombinant target enzyme and underwent a several-fold fluorescence increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
177
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(182 citation statements)
references
References 38 publications
4
177
0
1
Order By: Relevance
“…Peptide probes containing the Sox/C-Sox amino acid for a variety of kinases have been synthesized and implemented for kinase measurements with recombinant enzymes and in unfractionated cell lysates, yielding fluorescence enhancements of ~2-12-fold. [62][63][64] It was also found that substitution of the sulfonamide moiety on C-Sox by various substituted triazole groups (installed via click chemistry) gave rise to a multitude of novel Mg 2+ -chelating hydroxyquinoline FlAAs with fluorescence emission maxima that are shifted up to 40 nm. 65 These new click derivatives were incorporated into peptide substrates for study of the MK2 kinase and shown to be as efficiently turned over as C-Sox-containing peptides.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…Peptide probes containing the Sox/C-Sox amino acid for a variety of kinases have been synthesized and implemented for kinase measurements with recombinant enzymes and in unfractionated cell lysates, yielding fluorescence enhancements of ~2-12-fold. [62][63][64] It was also found that substitution of the sulfonamide moiety on C-Sox by various substituted triazole groups (installed via click chemistry) gave rise to a multitude of novel Mg 2+ -chelating hydroxyquinoline FlAAs with fluorescence emission maxima that are shifted up to 40 nm. 65 These new click derivatives were incorporated into peptide substrates for study of the MK2 kinase and shown to be as efficiently turned over as C-Sox-containing peptides.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…Both of these techniques provide useful information on whether the total amount of phosphorylated protein is increasing or decreasing over time; however, they do not directly measure new phosphorylation events or phosphorylation rates (12). MS techniques and fluorescence techniques have been developed to measure phosphorylation rates on synthetic peptides with known kinase consensus motifs in cell lysates (13,14). These techniques provide a read-out of kinase activity in cell lysates under different biological conditions.…”
mentioning
confidence: 99%
“…They often malfunction in disease states, such as cancer. Through interactions with colleagues at both MIT and other universities, Imperiali and her team fine-tuned the approach into a method that can screen kinase inhibitors and profile kinase activities in cell and tissue lysates (7,8). "The approach that we developed has been commercialized, and we are now looking towards ways to further development of the methods for diagnostic applications," she says.…”
Section: Measuring and Manipulating Biochemical Processesmentioning
confidence: 99%